2022
DOI: 10.20947/s0102-3098a0189
|View full text |Cite
|
Sign up to set email alerts
|

Redução do déficit de estatura e a compra de alimentos da agricultura familiar para alimentação escolar no Brasil

Abstract: O objetivo do artigo é analisar o efeito da compra direta de alimentos da agricultura familiar para alimentação escolar sobre o déficit de estatura em crianças menores de cinco anos, entre 2013 e 2017, no Brasil. O método utilizado é o estudo ecológico e longitudinal, em que a coleta de dados ocorreu em diferentes bancos de dados. A análise foi realizada por meio do teste t para amostras independentes, a fim de comparar as médias entre as variáveis déficit de estatura e compras da agricultura familiar. Além di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
2
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
1
2
3
Order By: Relevance
“…Black children had the highest prevalence of height deficit, a result consistent with the literature, given the worst health and nutrition conditions to which they are exposed 1,18,33 . However, the trend toward increased stunting observed in this study is inconsistent with the pattern of reduction of this condition that has been observed in Brazil in recent decades in different social groups [34][35][36] . We also observed that the annual increase in the prevalence of stunting occurred only in black children from the Southeast and South regions, reinforcing the hypothesis of the existence of racial inequality, resulting in greater nutritional vulnerability for these children.…”
Section: Discussioncontrasting
confidence: 99%
“…Black children had the highest prevalence of height deficit, a result consistent with the literature, given the worst health and nutrition conditions to which they are exposed 1,18,33 . However, the trend toward increased stunting observed in this study is inconsistent with the pattern of reduction of this condition that has been observed in Brazil in recent decades in different social groups [34][35][36] . We also observed that the annual increase in the prevalence of stunting occurred only in black children from the Southeast and South regions, reinforcing the hypothesis of the existence of racial inequality, resulting in greater nutritional vulnerability for these children.…”
Section: Discussioncontrasting
confidence: 99%
“…Black children had the highest prevalence of height deficit, a result consistent with the literature, given the worst health and nutrition conditions to which they are exposed 1 , 18 , 33 . However, the trend toward increased stunting observed in this study is inconsistent with the pattern of reduction of this condition that has been observed in Brazil in recent decades in different social groups 34 36 . We also observed that the annual increase in the prevalence of stunting occurred only in black children from the Southeast and South regions, reinforcing the hypothesis of the existence of racial inequality, resulting in greater nutritional vulnerability for these children.…”
Section: Discussioncontrasting
confidence: 99%
“…https://doi.org/10.1590/1980-549720230004 discordante do padrão de redução desse agravo que vinha sendo observado no Brasil nas últimas décadas em diferentes grupos sociais [34][35][36] . Ainda, observamos que o aumento anual na prevalência de déficit de estatura ocorreu apenas nas crianças pretas das regiões Sudeste e Sul, reforçando a hipótese de existência de desigualdade racial, repercutindo em maior vulnerabilidade nutricional para essas crianças.…”
Section: Discussionunclassified
“… 14 , 23 A policy of encouraging the purchase of food from family farming for school meals was seen to reduce the prevalence of stunting. 71 These studies illustrate how broad the determinants of this problem are.…”
Section: Methodsmentioning
confidence: 99%